Asymmetries in Global Value Chain Integration, Technology and Employment Structures in Europe: Country and Sectoral Evidence - Filippo Bontadini; Rinaldo Evangelista; Valentina Meliciani; Maria Savona (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper provides empirical evidence on the complex role played by technology in affecting the relationship between the participation of EU countries and industries in Global Value Chains (GVCs) and their employment structure over the period 2000-2014. The empirical analysis is based on country/industry level data for 21 EU countries on employment, trade in value added, patents and investments in intangible assets, and focusses on backward linkages within GVCs. The role of technology is analysed by taking into account both the technological intensity of offshoring industries and that of their GVC partners. We study the employment structure by looking at the shares of managers and manual workers, which reflect the “functional specialisation” of the country-sector within GVCs. We find that pre-existing asymmetries in the functional specialisation are highly persistent over time, with little sign of convergence over our observed period. Furthermore, GVC participation is not related to changes in the employment structure. However, this relationship appears to be mediated by country-industries' initial technological performance. Technological leader industries exhibit, in fact, larger shares of employment in headquarter functions, and this functional specialisation tends to be strengthened as they increase their integration into GVCs. In contrast, country-industries that start off as technological laggards see integration into GVCs accompanied by an increase in the share of employment in fabrication functions. The technological profile of the partners is also found to play a role in the relationship between GVC integration and the functional specialisation of the offshoring country/industry, although different patterns emerge depending on the nature of the partner (manufacturing vs service).
Keywords: F14; F15; O33; 330; global value chains; employment; technology; intangible assets; patents